Igrovoe povedenie v kommunikativnom prostranstve goroda - Kitajgorodskaâ Мargarita; Rozanova, Nina (Stylistyka, 2021)
The present paper is concerned with the everyday ‘world of laughter’. In it the communicative, spontaneous nature of everyday humor becomes most evident. The communicative method of research helps to reveal the process of a joke birth and to understand the mechanisms of its creation. Games, jokes, laughter of the contemporary citizen are fleeting and short-lived (as well as the routine of everyday life, which is usually ignored). That is why it is so important to collect facts, as they can be the basis for the revealing and conceptual interpretation of one of the most interesting and vivid forms of the language existence of the person. The study of the ‘laughing world’ of the everyday life and of its linguistic characteristics is one of the aspects of study of Russian culture. The material for the research was Moscovites’ speech. As a result of the recent overall political and socioeconomic restructuring, urban communication has significantly changed. It is characteristic of the modem Russian megapolis that contacts between strangers are established much more frequently. Among general tendencies in the change of urban communication there is the reinforcement of the dialogical nature of oral urban communication and of its individuality, and the revival of the ‘playing’ carnival element in the life of the city. Jokes and language games in everyday communication are inseparable from the situation (and often bom of it), they are communicative in their nature. A crucial factor for the realization of the ‘playing’ behavior is the orientation of the communication participants towards the ‘joking’ tone of the discourse, which is closely related to the parameters of space (inside the house/outside the house) and time (holidays/workdays). Further in the paper a variety of situation types, in which the ‘playing’ behavior of the citizens is realized in the most natural ways is realized, is considered. Special attention is paid to the market as a particular sociocultural space, the communicative peculiarities of which help the free manifestation of the ‘playing’ nature. In urban communication a number of situations emerging as reactions to various relevant events in the life of the society can be found in which ‘playing’ behaviour is realized. An example of such situations are meetings: in their communicative nature the features of folk street festivals and carnival can be observed. The liberation of the personal, ‘playing’ nature can be observed not only in the oral but also in the written form of urban communication in. An illustration is the changes of urban nominations. The communicative approach to the analysis of signboards reveals several important features distinguishing them from the nominations of the Soviet times. Among them there is the change in the nature of the role interaction between the sender (the namegiver) and addressee (the citizen), the change of the illocutionary goal of the words on signboards (from notification signs they changed into advertisement signs), as well as the change of their stylistic usage.